FAKTOR-FAKTOR YANG MEMPENGARUHI PELAKSANAAN MOBILISASI DINI PADA IBU POST SECTIO CAESARIA - ", Arjumiliza "; Dewi, Yulia Irvani; Elita, Veny " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
AbstractEarly mobilization is an attempt to maintain independence as early. Early mobilization is expected to improve blood flow so that it will accelerate the wound healing process. This study aims to find the factors that affecting the implementation of early mobilization of mother post caesarean with descriptive design correlation with cross sectional approach. Samples of this research were 43 respondents based on inclusion criteria using incidental sampling technique. Measuring instrument used was a questionnaire level of knowledge, information, pain scale, family support and motivation. Univariate analysis using to determine the frequency distribution and bivariate analysis using Chi Square test for the variable factors that affect the implementation of early mobilization. Univariate analysis of research result show the majority of mothers are in the age range 20-35 (90,7%), high education (37,2%), multigravida (65,1%), high level of knowledge (46,5%), the given information (53,5%), severe pain (46,5%), high family support (53,5%) and high motivation (51,2%). Bivariate analysis research shows that there is no relationship between knowledge (p value 0,078), information (p value 0,737) and pain scale (p value 0,078) to the implementation of early mobilization. Statistical test results between family support (p value 0,000) and motivation (p value 0,000) showed that there is a significant relationship to the implementation of early mobilization. Based on these results, it is suggested every inpatient room has the Standard Operating Procedure (SOP) on early mobilization. Keywords: support, mobilization, motivation, knowledge.